The Keynesian Diminisher - Braun, Eduard (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
The Keynesian expenditure multiplier is commonly viewed as a mechanism that amplifies expansionary fiscal or monetary policy. Once the assumptions on which the multiplier rests are applied to the classical quantity equation, however, it becomes obvious that the Keynesian multiplier is by far more pessimistic in this regard than the quantity equation. In light of this comparison, it makes much more sense to speak of the Keynesian “diminisher” than of the “multiplier.” The reason for the pessimistic bias of the multiplier can best be detected if the distinction is made between a one-time expansionary policy measure and a permanent one. It is only because of this pessimistic bias that the Keynesian “multiplier” can be used to justify permanent government spending programs.